Local Wisdom Of The Marind - Anim Tribe In Solving Social Problems And Its Impact On Building A Climate Of Religious Moderation In Merauke District - Resmin Manik (Jurnal Ad'ministrare, 2022)
The purpose of this study is to describe the mechanisms for solving social problems that are unique to the Marind-Anim tribe in Merauke Regency and to understand the nature of the informant's deepest world experience about an event or event based on the perspective of the informant. Understanding the phenomenon of what is experienced by research informants, for example, attitudes, perceptions, and actions holistically and using descriptions in the form of words and language, in a special natural context, and by utilizing various natural methods. The novelty of this study is the mechanism for solving social problems which is the peculiarity of the Marind-Animdi Tribe in Merauke Regency and the emic's view of the meaning of solving social problems in Merauke Regency, using a phenomenological qualitative research design. The role of traditional leaders and community leaders in the Marind-Anim tribe is known as Big Men or traditional leaders who have characteristics namely: 1) wealth, 2) courage, 3) ability to express opinions, 4) ability to organize, and 5) generosity. Big Men or traditional leaders are also reflected in their financial capabilities, such as having a large amount of money and large tracts of land. Financial adequacy allows them to be involved in politics to fight for positions at the village to provincial levels in an institution. Courage is the second characteristic of the Big Men or traditional leaders of the Marind-Anim Tribe in the process of social interaction within the community and institutions. Courage in the world of politics to put forward the interests of society and save people from inter-tribal wars that result in lives being lost. In addition, social problems that are very complex in Merauke Regency require courage and caution so that the strategy implemented can provide comfort to all elements of society at the local and national levels by prioritizing various local pearls of wisdom. The results of the study show that prioritizing local wisdom in deliberations is very effective in overcoming social problems both at the level of relatives, tribes, and the social environment as well as government through the Yamu Ritual and Api Sep which in the results in certainty and a sense of security, peace by burning symbols of mourning and wearing leaves again as a symbol of joy and brotherhood.Local wisdom; marindanim tribe; social issues; religious moderation.